Community health impacts of surface mining in the Upper West Region of Ghana: The roles of mining odors and dust. Issue 4 (19th May 2017) - Antabe, Roger; Atuoye, Kilian N.; Kuuire, Vincent Z.; Sano, Yujiro; Arku, Godwin; Luginaah, Isaac
ABSTRACT: The emergence of the gold mining industry and the influx of artisanal and small-scale mining following recent discoveries of gold deposits in Northern Ghana have posed new socio-cultural, economic, environment and health challenges for residents in this dry savannah zone that is already facing negative consequences of environmental change. Yet, the extent to which residents in close proximity (impacted) and distant (affected) host communities perceive the impact of mining on their health has been nascent. Using cross sectional survey data (n=801) and applying the negative log-log regression technique, we examine residents' self-rated health in mining communities in the Upper West Region of Ghana. The findings suggest that residents in impacted communities who believed that odors from mining activities could have health impact were twice more likely to report their health as poor, while those who were uncertain were 98% more likely to rate their health poor compared to those who disbelieved. However, sighting of dust was not significantly associated with subjective health in both impacted and affected communities. Based on these findings, it is recommended that Ghana's Minerals and Mining Act be reviewed to include the active involvement of host communities in mine leases while enforcing strict environmental best practices.